On the Right of Public Law Entities to Lodge a Constitutional Complaint in the Light of the Jurisprudence of the Polish Constitutional Tribunal - Kłopocka-Jasińska, Marta; Krzywoń, Adam (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The constitutional complaint entered into the Polish legal system under the Constitution of the Republic of Poland of 2 April 1997.The institution of constitutional complaint has been therefore in existence for nearly two decades and one might imagine that after this length of time a matter of such practical importance as delineating a group of entities entitled to lodge a constitutional complaint should cause no actual problems whatsoever. However, quite the opposite is in fact the case and the question of the capacity to file a constitutional complaint is still unresolved. It is open for discussion whether a constitutional complaint may be lodged by public law entities. The article deals with this problem, in particular, with the capacity of economic entities, units of local government and political parties. There are many arguments for enabling them, at least partially, to commence proceedings before the Polish Constitutional Tribunal.
Keywords: skarga konstytucyjna; podmioty prawa publicznego